2019
DOI: 10.1002/ame2.12054
|View full text |Cite
|
Sign up to set email alerts
|

Osteocyte viability and bone density in cadmium chloride‐induced osteoporosis ameliorated with Pilostigma thonningii stem bark‐extracted D‐3‐O‐methy‐chiroinositol

Abstract: Background This study examined the ameliorative effect of D‐3‐O‐methyl‐chiroinositol, isolated from the stem bark of Piliostigma thonningii , on cadmium chloride‐induced osteoporosis in male Wistar rats. Methods Thirty‐six rats were assigned to three treatment groups (n = 12). Group A (2 mL distilled water), group B: (2.5 mg/kg b.w. CdCl 2 ) and group C: (2.5 mg/kg b.w. CdCl 2 and D‐3‐O‐met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Other organs and cellular compartments such as testes (i.e., Sertoli, Leydig, and germ cells) (Zhu et al, 2020), osteocytes (Uwagie-Ero et al, 2019), cardiomyocytes (Chen et al, 2015), and peripheral and central nervous system (CNS; Wang and Du, 2013) also represent main targets of Cd toxicity. A recent meta-analysis has suggested that increased levels of Cd in human serum might play a pivotal role in neurodegenerative disorder progression (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Other organs and cellular compartments such as testes (i.e., Sertoli, Leydig, and germ cells) (Zhu et al, 2020), osteocytes (Uwagie-Ero et al, 2019), cardiomyocytes (Chen et al, 2015), and peripheral and central nervous system (CNS; Wang and Du, 2013) also represent main targets of Cd toxicity. A recent meta-analysis has suggested that increased levels of Cd in human serum might play a pivotal role in neurodegenerative disorder progression (Xu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The chosen dose for cadmium chloride was shown to cause significant oxidative stress in various tissues of the body (El-Demerdash et al, 2004;Alkhedaide et al, 2016) while that of GB1 showed significant antioxidant effect (Nwaehujor et al, 2013;Uwagie-Ero et al, 2019). Results of this study showed a significant (p<0.05) reduction in sperm count, sperm motility, number of morphologically normal spermatozoa and a significant (p<0.01) increase in the number of morphologically abnormal spermatozoa in Wistar rats exposed to cadmium chloride when compared to control and GB1-treated groups (Figure 2a-d…”
Section: Sperm Morphologymentioning
confidence: 99%
“…Its environmental accumulation is due to its increased industrial usage in mining, electroplating, dyeing, paints, just to mention a few, as well as its occurrence in agricultural fertilizers (Renugadevi and Prabu, 2009;Newairy et al, 2007). Cadmium is one of the elements found to damage antioxidant systems in mammals (Uwagie-Ero et al, 2019). In general cadmium pollution results from natural weathering of materials, forest fires and volcanoes, but much larger amounts are released by human activities (Morrow, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium is a nonessential element and is greatly harmful to the living body. Even at very low concentrations, cadmium can inhibit the growth of plants or even cause death. It is harmful to human health through contamination of the food chain, and the danger to animals is mainly manifested in the nervous system and kidney damage. Therefore, many efforts have been focused on studies about the mechanism of cadmium toxicity in plants and animals. Fortunately, some studies indicated that amino acids, such as proline, could help the plants in reducing the harm coming from the cadmium stress. …”
Section: Introductionmentioning
confidence: 99%